SiC/SiC-ZrSi2 coating with micro-pore to protect C/C composites against oxidation for long-life service at high temperatures. (October 2021) - Zhu, Xiaofei; Zhang, Yulei; Li, Honggang; Zhang, Jian; Fu, Yanqin; Su, Yangyang
Abstract: To improve the oxidation resistance of C/C composites for long-life service at high temperatures, a SiC/SiC-ZrSi2 coating with micro-pore was prepared by pack cementation and slurry, respectively. The coating could protect C/C composites for 1194 h at 1773 K in air with a mass gain of 1.42 wt.%. Such good antioxidant property was ascribed to the SiO2 -ceramic inlay structure with the ability of healing and covering the penetrating crack formed during oxidation, which had excellent oxygen diffusion resistance. Besides, the thermal stress was reduced by the micropores and the crack propagation was inhibited by ZrSiO4 particles. Highlights: The SiO2 -ceramic inlay structure is formed due to abundant SiO2 generated in the porous ceramic coating during oxidation. The SiO2 -ceramic inlay structure can prevent oxygen diffusion and heal the penetrating crack in the inner coating. The micropores can alleviate the thermal mismatch between the inner and outer coating. ZrSiO4 particles of the glass layer can inhibit the crack propagation.